DAMPAK PERTUMBUHAN EKONOMI INDONESIA PADA PERDAGANGAN INTERNASIONAL ANTARA INDONESIA – UNI EROPA - Zakiyatun Nuvus (Institut Agama Islam Agus Salim Metro Lampung, 2022)
This study aims to analyze the impact of international trade based on the value of exports and imports on Indonesia's economic growth. International trade is the activity of trading goods and or services carried out by residents of a country in meeting needs that cannot be produced independently. In IUU Fishing, it also aims to deal with or overcome illegal fishing, which is a crucial problem with large losses.Fishery products exported to the European Union encounter barriers and obstacles. The effect of growth on international trade. Large exports affect economic growth.